Dynamic response of high-performance honeycomb cores and hybrid fibre composite laminates for lightweight sandwich structures - Zhang, Yuwu (2018)
Lightweight sandwich structures that are composed of high–performance core and face sheets, have been attracting attention in both civilian and military applications due to their outstanding mechanical properties. Honeycomb cores and fibre reinforced composite face sheets have specific advantages for resisting dynamic impact. For example, honeycomb cores possess higher specific-strength (ratio of strength to relative density) than the other sandwich cores under compression, and carbon fibre composites possess high tensile strength and low density. This thesis focuses on the understanding of the dynamic compressive response of high-performance honeycombs and the ballistic impact resistance of stiff/soft hybrid fibre composite laminate beams. For honeycomb cores, the out-of-plane compressive behaviour of the AlSi10Mg alloy hierarchical honeycombs and commercially available Nomex honeycombs have been experimentally and numerically investigated. Owing to the complex in-plane topology, hierarchical honeycombs were fabricated using the Selective Laser Melting (SLM) technique. The experimental measurement and finite element (FE) calculation indicate that the two hierarchical honeycombs, specifically two-scale and three-scale honeycombs, both offer higher wall compressive strengths than the single-scale honeycombs. With an increase in relative density, the single-scale honeycomb experiences a transition in terms of failure mechanism from local plastic buckling of walls to local damage of the parent material. Alternately, the two-scale and three-scale hierarchical honeycombs all fail with solely parent material damage. The dynamic compressive strength enhancement of the hierarchical honeycombs is dominated by the strain rate sensitivity of the parent material. For Nomex honeycombs, the dynamic failure mode under out-of-plane compression is different from the quasi-static failure mode, i.e. the honeycombs fail due to stubbing of cell walls at the end of specimens under dynamic compression, whereas fail due to local phenolic resin fracture after elastic buckling of the honeycomb wall under quasi-static compression. The dynamic compressive strength of Nomex honeycombs increases linearly, and the strength enhancement is governed by two mechanisms: the strain rate effect of the phenolic resin and inertial stabilization of honeycomb unit cell walls. The inertial stabilization of unit cell walls plays a more significant role in strength enhancement than the strain rate effect of the phenolic resin. In addition, the effect of key parameters such as impact method and initial geometrical imperfections on the compressive responses of honeycombs has also been numerically investigated. For face sheets, the ballistic resistance of the beams hybridizing stiff and soft carbon fibre composites has also been experimentally studied, and these results were compared with those of stiff and soft composite beams with identical areal mass. The failure modes of composite beams under different velocity impacts have been identified to be different. For monolithic beams, the hybrid and soft monolithic beams exhibited similar energy absorption capacity. As for the sandwich beams, the hybrid sandwich beams behaved better in terms of energy absorption than soft sandwich beams at high projectile velocities. Both the hybrid and soft composite beams absorbed more kinetic energy from projectiles than stiff composite beams. The advantages of the stiff/soft hybrid composites can be summarized as follows: (i) the soft composite part survives at low velocity impact; (ii) the stiff composite part of the hybrid monolithic/sandwich beams has a more uniform stress distribution than the stiff monolithic/sandwich beams owing to the buffer effect of the soft composite part. This work identifies the advantages of high performance honeycomb cores as well as fibre composite face sheets. These findings can be used to develop high strength, low weight and multi-functional sandwich structures, thereby widening their applicability to a wider array of fields.